Legal Analysis of Access to Non-Formal Education for Street Children - Christian Felix Lumbanraja; Emmilia Rusdiana (Journal of Insan Mulia Education, 2025)
Education is a fundamental right guaranteed by the Constitution and various international legal instruments. However, street children often face limited access to formal education due to various social and economic factors. Non-formal education emerges as an alternative solution to ensure their right to education is fulfilled. This study aims to provide a legal analysis of street children's access to non-formal education in Indonesia by examining relevant regulations and identifying implementation challenges. The research adopts a normative legal method with a statutory and conceptual approach. The findings indicate that despite the existence of several regulations—such as the National Education System Law and the Convention on the Rights of the Child—there is no specific national regulation that governs non-formal education for street children, leading to a legal vacuum in ensuring their educational rights. The implementation of non-formal education also faces persistent obstacles, including limited funding, inadequate infrastructure, and a lack of coordination among stakeholders. Moreover, affirmative policies designed to accommodate the unique needs of street children in non-formal education remain suboptimal. Unlike previous studies that are mostly sociological or descriptive in nature, this article provides an in-depth legal analysis of the regulatory framework for non-formal education targeted at street children, as well as a critical evaluation of its implementation in the context of children's rights. The study concludes that strengthening specific regulations and enhancing synergy among the government, educational institutions, and the community are crucial to effectively and sustainably uphold the educational rights of street children.